Longitudinal effects of choir singing on aging cognition and wellbeing: a two-year follow-up study - Pentikäinen, Emmi; Kimppa, Lilli; Pitkäniemi, Anni; Lahti, Outi; Särkämö, Teppo (Frontiers in Human Neuroscience, 2023)
While increasing evidence points towards the benefits of musical activities in promoting cognitive and emotional well-being in older adults, more longitudinal studies are needed to establish their long-term effects and uncover the mechanisms through which musical activities affect well-being. Most previous research has focused on instrumental musical activities, but little is currently known about the long-term effects of singing, even though neuroimaging evidence suggests that it is a versatile activity for the brain, involving a multitude of neural processes that are potentially beneficial for well-being. We conducted a two-year follow-up study to assess aging-related changes in cognitive functioning and emotional and social well-being with self-report questionnaires and standardized tests in 107 older adult choir singers and 62 demographically matched non-singers. Data were collected at baseline (T1), and at one-year (T2) and two-year (T3) follow-ups using questionnaires on subjective cognitive functioning, depression, social engagement, and quality of life (QOL) in all participants and neuropsychological tests in a subgroup of 45 choir singers and 41 non-singers. The results of linear mixed model analysis showed that in verbal flexibility (phonemic fluency task), the choir singers had higher scores already at T1 and showed no change over time, whereas the non-singers showed enhancement from T1 to T3. Furthermore, active retrieval of word knowledge (WAIS-IV Vocabulary task) showed significantly different changes from T1 to T2 between the groups (enhancement in choir singers and decline in non-singers), however lacking significant change within groups. Similar opposite trajectories of QOL related to social inclusion and safety of the environment (WHOQOL-Bref Environmental subscale) were significant from T1 to T3, but changes were not significant within groups. Within the choir singers, shorter experience in singing was associated with greater improvement in the vocabulary task over the follow-up period, suggesting that initiation of singing at older age induces some verbal benefits. There were no group differences in any other questionnaire or neuropsychological measure over time. In conclusion, our results suggest that choir singing at older age is associated with a sustained enhancement of phonemic fluency, while the effects on other verbal skills and quality of life are less clear.